1970
DOI: 10.2141/jpsa.7.166
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Diet to Control Carcass Fat Deposition of Growing Chicks

Abstract: It was revealed in our previous papers1,2) that White Leghorn chicks younger than 4 weeks of age can easily become fatty with carcass fat of 17% in average or easily become lean with carcass fat less than 2%. Both fatty and lean chicks were obtained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1974
1974
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These results are in agreement with the reports of Yoshida et al (1966Yoshida et al ( , 1970 and Yoshida and Morimoto (1970a, b). These investigators used diets which contained extremely high and low protein concentrations and some of their experiments were performed with Leghorn chicks.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with the reports of Yoshida et al (1966Yoshida et al ( , 1970 and Yoshida and Morimoto (1970a, b). These investigators used diets which contained extremely high and low protein concentrations and some of their experiments were performed with Leghorn chicks.…”
Section: Discussionsupporting
confidence: 94%
“…Through these studies it was established that, as the dietary C : P ratio was widened, energy intake and carcass fat deposition increased, while body water content decreased. Yoshida et al (1966Yoshida et al ( , 1970 and Yoshida and Morimoto (1970a, b) have reported that the effect of dietary protein concentration on carcass fat content is rapid and reversible. Thomas and Twining (1971), too, observed considerable changes in carcass fat content, as early as 10 d after alterations were made in protein concentrations.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…To examine the reliability of a method for the control of protein and energy retentions in the carcass, the authors compared the amounts of protein and energy retentions measured by carcass analysis (denoted as measured value in the text) in rats given 9 diets shown in Table 1 with the amounts of protein and energy retentions calculated (denoted as calculated value in the text) by putting the values of DCP and ME intakes shown in Table 1 into multiple regression equations (1) and (2).…”
Section: Reliability Of a Methods For The Control Of Protein And Energmentioning
confidence: 99%
“…Through the subsequent studies (BARTOV et al, 1974;COMBS et al, 1964: EDWARD'S andHART, 1971;SPRING and WILKINSON, 1957;SKINNER et al, 1992;SUMMERS et al, 1965;YOSHIDA et al, 1970), it has been established that fat increase in practical type diets unavoidably causes excessive energy consumption because feed intake decline is not proportional to the increase of dietary energy density.…”
Section: Introductionmentioning
confidence: 99%